Whole transcriptome analysis of unmutated sporadic ALS patients' peripheral blood reveals phenotype-specific gene expression signature - Francesca Dragoni; Maria Garofalo; Rosalinda Di Gerlando; Bartolo Rizzo; Matteo Bordoni; Eveljn Scarian; Camilla Viola; Veronica Bettoni; Giuseppe Fiamingo; Danilo Tornabene; Lucia Scanu; Orietta Pansarasa; et al. (Neurobiology of Disease)
Amyotrophic lateral sclerosis (ALS) is an adult neurodegenerative disorder. According to clinical criteria, ALS patients can be classified into eight subgroups: classic, bulbar, pyramidal, pure lower motor neuron, flail arm, pure upper motor neuron, flail leg, and respiratory. There are no well-established molecular biomarkers for early diagnosis, prognosis, and progression monitoring of this fatal disease. Classification based on clinical phenotypes could be associated with peculiar gene expression patterns shaped during lifespan, allowing the identification of specific sporadic ALS (sALS) subtypes with less heterogeneous clinical and biological features. Our objective was to define a phenotype-specific transcriptomic signature of distinct ALS phenotypes, and lay the foundation for biomarkers development. We characterized 48 sALS patients by clinical and paraclinical parameters, and subdivided them in “Classic” (n = 12), “Bulbar” (n = 10), “Flail Arm” (n = 7), “Flail Leg” (n = 10) and “Pyramidal” (n = 9) phenotypes. RNAs extracted from patients' PBMCs and 19 controls were sequenced. Our analysis allowed the visualization of gene expression differential clusters between patients and controls. Interestingly, only one gene (Y3_RNA, a misc_RNA component of the Ro60 ribonucleoprotein involved in cellular response to interferon-alpha) was upregulated at different levels across all phenotypes, whereas other genes appeared phenotype-specific. The work proposed stress the innovative view of ALS as a multi-systemic disorder rather than a pure motor neuron-associated and ‘neurocentric’ pathology. The possibility to cluster ALS patients based on their molecular signature pave the way for future personalized clinical trials and early diagnosis.